2022
DOI: 10.3390/atmos13060983
|View full text |Cite|
|
Sign up to set email alerts
|

Landfill Emissions of Methane Inferred from Unmanned Aerial Vehicle and Mobile Ground Measurements

Abstract: Municipal solid waste landfills are significant sources of atmospheric methane, the second most important greenhouse gas after carbon dioxide. Large emissions of methane from landfills contribute not only to global climate change, but also to local ozone formation due to the enhancement of radical chain lengths in atmospheric reactions of volatile organic compounds and nitrogen oxides. Several advanced techniques were deployed to measure methane emissions from two landfills in the Southeast Michigan ozone nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The results of the waste composition analysis showed that plastic had the dominant value of 43.56%, followed by paper waste of 22.99%, wood and straw waste 14.76%, garden waste 11.23%, textiles 4.61%, disposable nappies 2.85% and food waste 0.73%. This result is similar to several studies which show that plastic waste is the most dominant waste among inorganic waste [10] [24] [25].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation

Environmental Impact Analysis of Methane Gas from Landfill using LCA in Klotok landfill, Kediri, East Java

Restu Hikmah Ayu Murti,
Muhammad Abdus Salam Jawwad,
Syadzadhiya Qothrunada Zakiyayasin Nisa
et al. 2023
Technium
“…The results of the waste composition analysis showed that plastic had the dominant value of 43.56%, followed by paper waste of 22.99%, wood and straw waste 14.76%, garden waste 11.23%, textiles 4.61%, disposable nappies 2.85% and food waste 0.73%. This result is similar to several studies which show that plastic waste is the most dominant waste among inorganic waste [10] [24] [25].…”
Section: Resultssupporting
confidence: 92%
“…The second most important greenhouse gas after carbon dioxide is methane, and municipal solid waste dumps are substantial contributors to its presence in the atmosphere [9]. Significant methane emissions from landfills contribute to global climate change and the development of ozone caused by the augmentation of radical chains that occur in atmospheric reactions of volatile organic compounds and nitrogen oxides [10]. This results from methane emissions, which make the chain lengths of radicals in the environment longer [11].…”
Section: Methane Landfill Emissionmentioning
confidence: 99%

Environmental Impact Analysis of Methane Gas from Landfill using LCA in Klotok landfill, Kediri, East Java

Restu Hikmah Ayu Murti,
Muhammad Abdus Salam Jawwad,
Syadzadhiya Qothrunada Zakiyayasin Nisa
et al. 2023
Technium
“…Compared with traditional OP-TDL systems, the sTDLAS detector measures the cumulative gas concentration across the entire beam, collecting information over a large area with a single measurement [5]. Lightweight TDLAS sensors optimized for use on UAVs (weight: 0.53-2 kg) were tested in six studies [38][39][40][41][42][43] to measure CH 4 .…”
Section: Platforms and Sensing Technologies For Uav-based Chemical Se...mentioning
confidence: 99%
“…Such regulations caused SEM data to become the most abundant data related to methane emissions in US landfills. Surface emission monitoring (SEM) can be performed by employing walking-based measurements (using FID or equivalent equipment) or by employing newer methodologies and technical advances offered through UAVs such as drones [12][13][14]. Ground-based (G-SEM) campaigns are performed using relatively affordable equipment.…”
Section: Introductionmentioning
confidence: 99%
“…With the abundance of SEM data arises the question of how to make better use of surface concentration measurements to locate emission sources and infer an estimate of methane emissions at the monitored landfills, in other words, how to transform measured methane concentrations (in ppmv) to an estimate of the emission rate (in Kg/h). Some researchers tried to establish simple correlation equations linking surface methane concentrations to emission rates [12,13]. Ref.…”
Section: Introductionmentioning
confidence: 99%